IMPLIKASI ISLAM UNTUK PESAN IKLAN: KONTEKS TIMUR TENGAH - Ramadini, Ulla; Najah, Fitriatun; Muhammad, Muhammad (LP2M IAIN Palangka Raya, 2011)
Â Islam is the great religion and develops among the consumers all over the world. There is an evidence that the religious beliefs influence the consumersâ behaviors and responses toward the message of the advertisement. The objective of the article is to present a framework in managerial decision making related to Islamic values toward the implication of illustrated advertisement in the context of Middle East. The recommendation is provided for international advertisement to develop the messages for the segmentation of Muslim consumers.Â